1972
DOI: 10.1038/bjc.1972.51
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Responses of Prostatic Carcinoma to Testosterone in Organ Culture

Abstract: Summary.-Slices of human prostatic adenocarcinoma obtained by transurethral resection were maintained in organ culture for 4 days. Preservation of histological appearance was good with little evidence of necrosis within the viable tissue. Slices of tumour cultured in the presence of testosterone showed a morphological change to a more differentiated type of neoplasm whereas explants cultured in the absence of steroid hormone, or with stilboestrol diphosphate, showed no change. In the case of a relatively anapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Supplementation of the culture medium with testosterone and dihydrotestosterone caused the number of labeled epithelial cells to rise from the 74% observed in medium without supplementation to 88% and 92% in the cul-tures that contained these androgens; in addition (Lasnitzki et al, 1975), "testosterone and dihydrotesterone raised the grain counts by approximately 50% over those seen in the controls whereas oestradiol reduced them by 35%." Conclusions about the effects of various hormones on the organ culture of hyperplastic prostates have been variable (Kadohama and Sandberg, 1988;Lasnitzki et al, 1975;McMahon and Thomas, 1973;McMahon et al, 1972;McRae et al, 1973), and the quantification of these results has been imprecise; however, many investigators have found that androgens result in some, often small, improvements in the quality of the cultured cells. At the opposite extreme, Harbitz et al (1974) concluded that "benign nodular hyperplasia of the prostate seems to be essentially unaffected by steroid hormones in shortterm [3-dayl organ culture experiments."…”
Section: Organ Culture Of Human Prostatesmentioning
confidence: 99%
“…Supplementation of the culture medium with testosterone and dihydrotestosterone caused the number of labeled epithelial cells to rise from the 74% observed in medium without supplementation to 88% and 92% in the cul-tures that contained these androgens; in addition (Lasnitzki et al, 1975), "testosterone and dihydrotesterone raised the grain counts by approximately 50% over those seen in the controls whereas oestradiol reduced them by 35%." Conclusions about the effects of various hormones on the organ culture of hyperplastic prostates have been variable (Kadohama and Sandberg, 1988;Lasnitzki et al, 1975;McMahon and Thomas, 1973;McMahon et al, 1972;McRae et al, 1973), and the quantification of these results has been imprecise; however, many investigators have found that androgens result in some, often small, improvements in the quality of the cultured cells. At the opposite extreme, Harbitz et al (1974) concluded that "benign nodular hyperplasia of the prostate seems to be essentially unaffected by steroid hormones in shortterm [3-dayl organ culture experiments."…”
Section: Organ Culture Of Human Prostatesmentioning
confidence: 99%
“…Testosterone metabolism was thought to provide a sensitive index by which to evaluate changes in culture conditions. It has been found possible to maintain human prostatic slices in organ culture so that the morphology of the cultured expiants resembled that of the fresh tissue (McMahon et al 1972; McMahon Se Thomas 1973). To achieve greater confidence in this experimental model it is desirable to demonstrate similarities ') Present address:…”
mentioning
confidence: 99%
“…Recent work in this laboratory has shown that carcinoma of the prostate and benign prostatic hyperplasia (McMahon, Butler and Thomas, 1972) can be cultured successfully using a modification of the grid technique (Trowell, 1959), the main innovation being that a slab of agar-gelled medium was interposed between the explant and the grid. The use of a sheet of 2% agar in 0.7 % NaCl, as an alternative to lens tissue, was originally suggested by Trowell (1959) (McMahon, 1970).…”
Section: Discussionmentioning
confidence: 99%